PERANCANGAN SISTEM MANAJEMEN PENGETAHUAN UNTUK PENELITI DI PUSLITBANG APTIKA DAN IKP - Andriariza, Yan (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
Puslitbang Aptika IKP have 8 researchers, and 3 candidate researchers. In conducting the study, there were a lot of knowledge needed to support the research being conducted. This is why, importance to manage knowledge in Puslitbang Aptika IKP. To manage knowledge, Puslitbang Aptika IKP can build a Knowledge Management System as a means to develop knowledge among researchers in the Puslitbang Aptika IKP which is based on the application of web 2.0. Web 2.0 itself is aimed so that the researchers can manage each of the knowledge they have to share with other researchers. The methodology used in this study are based on the methods used by Amrit Tiwana, which in this study was only done just the second stage, that stage is Analysis, Design and Development of Knowledge Management Systems. Methods of data collection using observation and Literature. The final results of this study showed that the use case consists of 4 main activities, namely search, management, knowledge management and user management, and there are 2 actors are researchers and IT staff. In class diagram there are 17 classes that are connected between the one with the other